If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(11 + -4c) = 11(c + -9) (11 * -2 + -4c * -2) = 11(c + -9) (-22 + 8c) = 11(c + -9) Reorder the terms: -22 + 8c = 11(-9 + c) -22 + 8c = (-9 * 11 + c * 11) -22 + 8c = (-99 + 11c) Solving -22 + 8c = -99 + 11c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-11c' to each side of the equation. -22 + 8c + -11c = -99 + 11c + -11c Combine like terms: 8c + -11c = -3c -22 + -3c = -99 + 11c + -11c Combine like terms: 11c + -11c = 0 -22 + -3c = -99 + 0 -22 + -3c = -99 Add '22' to each side of the equation. -22 + 22 + -3c = -99 + 22 Combine like terms: -22 + 22 = 0 0 + -3c = -99 + 22 -3c = -99 + 22 Combine like terms: -99 + 22 = -77 -3c = -77 Divide each side by '-3'. c = 25.66666667 Simplifying c = 25.66666667
| 24x^3-36x^2+48x= | | 27x^9-y^3= | | 5x+9=3x+31 | | 14.75+1x=75 | | 3y(4y-1)-2y(6y-5)=9y-8(3+y) | | s=68-20log(14+1) | | 2x(2)+9x-7=0 | | 6x^2+19x=-10 | | 5(4m-7)(m-4)=0 | | 8.5+9.4= | | 6y+8=5y-8 | | 2x=45-4x | | 24x-6x(13x-9)=-13-13x(6x-1) | | -9x+15=-22-14(x+12) | | (r+2)2=0 | | 14.75+1x=50 | | 3x(2x-1)-6x(7+x)=90 | | 4t^3-3t=0 | | 16y^2-18y-9=0 | | x^2-15x-216=0 | | 9x^3+45x^2-25x-125=0 | | .5(2y-1)-(.5-.2y)+1=0 | | x+6-5x=180 | | 5=-(2+6t)-t | | 7x+4x-6x=8x | | (3x+2)(5x^2-16x+12)=0 | | 59=50+(n-40)/4 | | 4(5x+4)=24(x-1) | | 2z+3=76 | | 5x-8=13++7(x-3) | | -11=14-2h | | 4(5y-2)+3(2y+6)=25(3y+2)-19y |